Arcademis: um arcabouço para construção de sistemas de objetos distribuídos em Java - Fernando Magno Quintao Pereira (2004)
This master dissertation presents Arcademis: a framework for middleware development. This framework is constituted by a set of Java classes and interfaces, plus some concrete components that can be extended or assembled together in order to build middleware platforms that support several di®erent requirements and scenarios. A middleware system, obtained from Arcademis, is also presented. This platform, called RME, provides J2ME, the Java distribution for embedded and mobile devices, with a remote invocation service. This service targets CLDC, a particular con¯guration of J2ME that does not support the Java re°exivity features.